THE EAST HINDIA COMPANY'S TRADE AND THE MOESLIM ECONOMY IN THE MUGHAL SULTANATE OF INDIA, 1610-1630 AD - Abdurrahman, Dudung; Luqman Al Hakim; Ilhamzah; Muhammad Muzir Azyumardi (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
The Mughal Sultanate was one of the great Islamic sultanates in the classical Islamic era, the Mughal contribution to Islamic civilization in India was very large in terms of politics, culture, architecture, and economy. In the economic field, the Mughals had been independent before the arrival of the EIC in the sultanate in 1610, the Mughals had exported a lot of their agricultural and mining products to both Asia and Europe by cooperating with Muslim merchants, as well as land rulers both Muslim and Hindu. The arrival of EIC in the Mughal Sultanate changed the existing economic order because EIC in smoothing its business often entered into contracts with landlords and bribes with the Mughal apparatus it had significant implications for the development of the Islamic economy in the Mughal Sultanate. EIC also played a monopoly in India and outside India, resulting in the death of the Islamic economy. Eventually, many Muslim merchants and landlords turned to EIC for the sake of their business.